Odpowiedzi

2009-09-26T20:42:12+02:00
X do kwadratu -6 / 5x - 5 * x/x = x-1/ x+2 + x+3/ x-2 - 3x-1/ x do kwadratu -4 /*4
4* x do kwadratu -6/ 5x-5 * 4* x/x = 4* x-1/x+2 + 4* x+3/x-2 - 4* 3x-1/x do kwadratu -4
4x do kwad. -6/ 5x-5*4= 2x-2/x + 2x+6/6 - (-3x+1)/x do kwad.

4x do kwad.-24/5x-5 *4= 12 - (-3x+1)/x do kwad.
20x do kwad. -96/5x-5= 12 - (-3x+1)/x do kwad. / *(5x-5)
20x do kwad. -96=60x-60- (-15x do kwad.-15x+5x-5)/x do kwad. 20x do kwad. -96=60x-60-(-15)-10x
20x do kwad.-96=60x-45-10x-5
20x do kwad.-96=50x-50
20x do kwad.-50x=-50+96
20x do kwad.-50x=46 / :(-x)
-20x+50=-46
-20x=-96 / :(-20)
x=96/20
x=4i4/5



/ - oznacza kreskę ułamkową